2019
DOI: 10.3390/molecules24193495
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Fluorescence-Based Assay for the Detection of Sucrose Transport and the Introduction of a Sucrose Transporter from Potato into Clostridium Strains

Abstract: A convenient and effective sucrose transport assay for Clostridium strains is needed. Traditional methods, such as 14C-sucrose isotope labelling, use radioactive materials and are not convenient for many laboratories. Here, a sucrose transporter from potato was introduced into Clostridium, and a fluorescence assay based on esculin was used for the analysis of sucrose transport in Clostridium strains. This showed that the heterologously expressed potato sucrose transporter is functional in Clostridium. Recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 38 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…Open Sci. 8: 201858 competes with esculin for transport into recombinant strains [22]. The fermentation results in the present study confirmed that StSUT1 induced sucrose transport in C. beijerinckii.…”
Section: Effective Sucrose Transport For Improved Abe Fermentationsupporting
confidence: 84%
See 4 more Smart Citations
“…Open Sci. 8: 201858 competes with esculin for transport into recombinant strains [22]. The fermentation results in the present study confirmed that StSUT1 induced sucrose transport in C. beijerinckii.…”
Section: Effective Sucrose Transport For Improved Abe Fermentationsupporting
confidence: 84%
“…The StSUT1 gene, encoding a sucrose transporter from potato, was expressed in C. beijerinckii . The sucrose transport activity in the engineered strains was assayed using a previously described method [ 22 ], in which highly fluorescent esculin, a structural analogue of sucrose, was used as a probe to characterize sucrose transport activity [ 29 , 30 ]. Strain 13-4 was wild-type strain screened from molasses medium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations